A Research Review of the Concepts, Necessity and Importance of Prophetic Medicine - Attiya Khaliq; Dr.Zafar Ali (Corresponding Author) (`, 2025)
Prophetic medicine is an ancient method of treatment. Its uniqueness from other methods of treatment is that it is a divine method of treatment in which the Creator has revealed the solution to the medical problems of His creation. Prophetic medicine (peace be upon him) is essential for the continuation of human existence. And Prophetic medicine (peace be upon him) is important for the preservation of human existence. Illness is related to every aspect of human life. Similarly, when treating mental illnesses, mental life is related to Prophetic Medicine. In Prophetic Medicine (PBUH), mental and psychological health of a person is as important as physical health. Prophetic Medicine (PBUH) is not just about treating illness, but also about measures and food that can build immunity before the onset of illness. This is also part of Prophetic Medicine (PBUH). Prophetic Medicine (PBUH) is an ancient method of treatment. Its uniqueness from other methods of treatment is that it is a divine method of treatment in which the Creator has revealed the solution to the medical problems of His creation. Prophetic Medicine (PBUH) is essential for the survival of humanity. And Prophetic Medicine (PBUH) is important for the preservation of humanity. Keyword: Medicine, Prophetic Medicine, Meaning, Necessity, Importance, Medicine, Scope.